Contexto multilíngüe: conduta avaliativa e atitudes lingüísticas. A influência de crenças e políticas - Finger, Leila (Contingentia, 2008)
Based on the bilingualism and ethnolinguistic identity research, this study aims to observe the role identity and linguistic attitudes play in a minority mother language’s maintenance or shifting process in early bilingualism cases in a societal bilingualism situation. The analyzed context comprises native speakers of essentially bilingual communities that migrate to an urban center like Porto Alegre, where the opportunities for minority mother language use are drastically restrained by the monolingual Portuguese context. It’s asked how this language was maintained and what is the identity and linguistic attitude after the removal of the original context identified as more rural, isolated and ethnic and culturally different. The data collection derives from semi-structured interviews, recorded and subsequently transcribed. The data analysis suggests that the ‘geographic’ factor isn’t so relevant to the maintenance/shifting of a minority language than the speaker’s ‘micro-decisions’ to preserve the cultural and affectionate ties with their origin group, the family. Besides family group, community, school and government should be called to come together to construct new ways for the linguistic and cultural preservation of the bilingual community in Brazil. In that sense, this research intends to contribute to a wider understanding of the identity and linguistics attitudes’ role in the languages’ teaching and learning in general.